On The Role of Strategies in The Development of Organizations And the National Economy - Valery Maksimovich TUMIN; Elena Vyacheslavovna ZENKINA; Petr Aleksandrovich KOSTROMIN; Valery Valerievich TUMIN; Anastasia Alekseevna GUKOVSKAYA (Communications of International Proceedings, 2022)
The article describes the key problems of the Russian economy in the context of strategic development. The structure of budget revenues and the share of venture investments in GDP are analyzed. It is noted that the disproportions in development are caused by the priority of short-term tactical management decisions over strategic goals of long-term development. Solving problems is complicated by the transformation of the essence of organizations towards the growth of intangible business models using digital technologies and distributed network management technologies. Moreover, some types of strategies, for example, commodity and grocery ones, are also changing, as new types of goods of symbolic value appear. The authors conclude that organizational, sectoral and territorial, state and supranational strategies need to be implemented in a single system. At the same time, the strategy should be considered as a set of strategic decisions that affect the microenvironment, as well as the near and far macroenvironment of the organization.
Keywords: strategic management; organization development; national economy; business model